Prognostic value of histological activity in patients with ulcerative colitis in deep remission: A prospective multicenter study. Issue 5 (1st June 2018) - Lobatón, Triana; Bessissow, Talat; Ruiz-Cerulla, Alexandra; De Hertogh, Gert; Bisschops, Raf; Guardiola, Jordi; Van Assche, Gert; Vermeire, Severine; Ferrante, Marc
Abstract : Background: Histological remission has been proposed as a new treatment goal in patients with ulcerative colitis (UC) although no universal definition for microscopic activity exists. Aim: We evaluated the accuracy of histological activity to predict clinical relapse in UC patients with both clinical and endoscopic remission. Methods: Asymptomatic UC patients in endoscopic remission (Mayo endoscopic sub‐score 0 or 1) undergoing surveillance colonoscopy in two referral hospitals were prospectively recruited. All colonic biopsies were analyzed according to the Geboes' score (GS) and the presence of basal plasmacytosis (BP). Results: Ninety‐six patients were included (38% women, median (interquartile range) age 50.0 (39.0–58.5) years, median disease duration 12.0 (6.5–19.5) years). Histological activity defined as GS ≥ 2B.1, GS ≥ 3.1, or BP was present in, respectively, 26%, 23% and 12%. Within 12 months from index endoscopy, 23% of the patients presented with clinical relapse. In multivariate analysis, active histological disease was the only risk factor predicting clinical relapse (odds ratio (95% confidence interval) 4.29 (1.55–11.87); p  = 0.005 for GS ≥ 2B.1 and 4.31 (1.52–12.21); p  = 0.006 for GS ≥ 3.1). Conclusions: In patients with UC in clinical and endoscopic remission, histological activity is an independent risk factor for clinical relapse. Further prospective studies need to clarify whether treatment optimization is justified in this context.